Wales anaerobic test: reliability and fitness profiles of international rugby union players - Beard, A.; Ashby, J.; Chambers, R.; Millet, G. P.; Brocherie, F. (The Journal of Strength and Conditioning Research, 2022)
To provide strength and conditioning coaches a practical and evidence-based test for repeated-sprint ability (RSA) in rugby union players, this study assessed the relative and absolute test-retest reliability of the Wales Anaerobic Test (WAT) and its position-specific association with other fitness performance indices. Thirty-four players (forwards: n = 19; backs: n = 15) of the Welsh rugby union male senior national team performed the WAT (10 × 50-m distance, 25-30 seconds of passive recovery) twice within 4 days. Time for each repetition was recorded, with the best (WATBest) and total time (WATTT) retained for analysis. Relative (intraclass correlation coefficient [ICC]) and absolute (SEM) reliability of the WAT indices were quantified. Furthermore, association (Pearson's product-moment correlations and stepwise backward elimination procedure) with other fitness performance indices (10- and 40-m sprinting times, 30-15 intermittent fitness test [30-15IFT] and the Yo-Yo intermittent recovery test level 2 [YYIR2]) was investigated. Pooled values revealed "moderate" to "high" ICCs for WATBest (ICC = 0.89, p = 0.626) and WATTT (ICC = 0.95, p = 0.342). Good test sensitivity was reported for forwards and backs' WATTT (p > 0.101). Both WATBest and WATTT correlated with 10-m and 40-m sprinting times (r > 0.69, p < 0.001) as well as with 30-15IFT (r < -0.77, p < 0.001) and YYIR2 (r < -0.68, p < 0.001) for pooled values. The WAT proved to be a reliable and sensitive test to assess the rugby union specific RSA-related fitness of international players.